BIM critical factors and benefits for public sector: from a systematic review to an empirical fuzzy multicriteria approach - Schery, Carlos Alejandro Díaz; Vignon, Yiselis Rodríguez; Caiado, Rodrigo Goyannes Gusmão; Santos, Renan Silva; Congro, Marcello; Thadeu Corseuil, Eduardo; Roehl, Deane (Brazilian Journal of Operations & Production Management, 2023)
Goal: The purpose of this study is to develop a decision support framework to select critical success factors (CSFs) and benefits for the implementation of BIM in the public works sector. Design / Methodology / Approach: The research methodology integrates multiple fuzzy multicriteria decision making (MCDM) approaches to propose a composite framework of CSFs and benefits using qualitative and quantitative approaches, with the application of two semi-structured questionnaires with CSFs and benefits identified in previous studies, through a systematic literature review (SLR). Results: The study identified 42 CSFs and 31 benefits for the implementation of BIM for public works, and the relative importance of the identified factors and benefits was measured according to the four main BIM perspectives: legal, people, process, and technology. The result of the applied MCDMs showed the relationship between the factors and benefits of the four most influential BIM perspectives according to the proposed framework. The most influential CSFs and benefits were: BIM adoption requires individual and group motivation in the organization, Establishment of BIM and Lean construction standards, codes, rules, and regulations, Financial support from the government to establish BIM system, Availability of quality, schedule, and cost information during construction with BIM Accuracy and reliability of documents and data and BIM provides knowledge sharing among stakeholders, Workflow, productivity, and efficiency are affected by the transition to BIM, BIM technology reduces cost and time, Conflict detection, integration, coordination, and design validation, and Creating more efficient projects with stakeholder involvement, coordination, and oversight. Limitations of the investigation: The research sample consisted exclusively of Brazilian professionals and academics with experience in the implementation of BIM in public works. Practical implications: The proposed framework can be applied in implementation in public construction projects that aims to implement BIM considering the selection of critical success factors and benefits. Originality / Value: BIM methodology is widely used in the construction industry. However, there are few studies on CSFs and the benefits of BIM for the public sector, and there still lack of implementation frameworks proposal with empirical evidence.